(3feGPL h JWHjbGJ aj EOGQI GdCYeGd h GdJShjbs - (3gjKe(B, (3GdTHdjs ((3YeGf(B:s (3OGQ UaGA ddfTQ hGdJhRjY(B,s, 2009)
(3deMI JGQjNjI Yf JWhQ GdMGShH h eLGdGJ GSJNOGeg h GdNhGQjRejGJ h eNWWGJ SjQ GdYedjGJ, CfXeI GdJTZjd, eYGdL GdfUhU ejcQhShaJ hhQO, JWHjbGJ eYGdL GdfUhU (Bword (3aj GdYdhe GdGOGQjI h GdJShjb, HQfGeL EcSd h JWHjbGJg aj GdYdhe GdGOGQjI h GdJShjb, GdJMdjd h GdJfHD GdJShjbjs
Keywords: (3EOGQI GdCYeGds; (3GdJShjbs; (3GdMGSHGJ GdEdcJQhfjIs